Synthesis and antifungal activities of 5-substituted-arylimino-2-N- substituted-phenyl-3-oxo-1,2,4-thiadiazolidines - Manna P.; Narang K.K. (My University, 2025)
5-Substituted-arylimino-2-N-substituted-phenyl-3-oxo-1,2,4-thiadiazolidines (IVa-e) have been synthesized by oxidative debenzylation and cyclization with molecular bromine in moistened chloroform from the corresponding 1-substituted-aryl-5-substituted-phenyl-2-S-benzyliso-4-biurets (IIIa-e) in moderate yield. Biurets, in turn, were prepared by the condensation of 1-substituted-aryl-2-S-benzylisocarbamides (IIa-e) and substituted-phenyl- isocyanate. These thiadiazolidines have been characterized by element analysis, IR, 1H-NMR, 13C-NMR and mass spectra. Anti-fungal screening of the title compounds against ten fungi have been carried out by glass slides method and their comparative findings have been critically examined and reported. The compound possessing methoxy group at p-position in one aryl ring and dichloro group in another aryl ring (IVe) has shown maximum inhibition (99.5%) against Aspergilus pisi at 1000 g/mL concentration.